O texto publicitário na sala de aula - Santos, Hérika Ribeiro dos (2007)
Approach in publicity text genre given in three different textbook collections has been investigated in current qualitative and ethnographic research. Theoretical basis has been mainly foregrounded on the theory of genres by precursor Mikhail Bakhtin and followers Marcuschi, Bronckart, Pasquier, Dolz, Dionísio, Schneuwly and Rojo. After a detailed study on the Brazilian School Curriculum Parameters with regard to Portuguese language teaching, the theoretical proposal given in the teacher's handbook of each collection was undertaken in the publicity genre. Parameters consisted of reading, writing production, orality and linguistic analysis. Chapters dealing with publicity genre were analyzed and then compared to theory to verify whether the latter was put in practice in the activities suggested. Assets and defects in the chapters were consequently identified. Teachers who adopted the book collections in the classroom were interviewed to see whether defects had been pinpointed and to diagnose how they supplemented for the gaps within the texts. Results show that (1) the books contain issues at different levels dealing with the educational training of the citizen, the reader and the teacher, even though incoherence between theory and practice is extant; (2) teachers are frequently knowledge multipliers since they fail to act in favor of transformation, even when gaps are detected, and continue year after year to reproduce paradigms held to be unquestionable truths.